Formulation and Evaluation of Nanosponges Loaded Hydrogel of Metformin Hydrochloride - Pawar, Ashish Y; Jadhav, Khanderao R; Rathod, Sharayu P; Sanap, Ashwini S; Umekar, Milind J (Indian Journal of Pharmaceutical Education and Research, 2023)
Objectives: The objective of the research is to formulate a nanosponges loaded hydrogel of Metformin Hydrochloride for the treatment of Psoriasis. Psoriasis is currently treated with a variety of topical and systemic therapies. Many of these treatments, however, are expensive and involve side effects, such as immunosuppression. As a result, there is a need to develop therapies that are effective, have fewer adverse effects, and are less expensive. Materials and Methods: The Solvent Emulsion Diffusion Process was used to create Metformin Hydrochloride nanosponges. Ethyl cellulose was used as a polymer, polyvinyl alcohol was used as an emulsifying agent, and an organic solvent mixture of Dichloromethane and Ethanol (1:1) was used to make nanosponges. The optimized batches of nanosponges were used for the formulation of Hydrogels using different gelling agents like Carbopol 934, HPMC K4, Sodium alginate and Acacia with same concentration. Results: The formulated Metformin Hydrochloride nanosponges were characterized by various tests like the Production yield, Entrapment efficiency, FT-IR, Zeta potential, Scanning Electron Microscopy, etc. Batch F5 showed the highest entrapment efficiency with the lowest particle size and hence was considered as the optimized batch for the formulation of the Hydrogels. The FT-IR ensured the compatibility of the drug with the polymer, the Zeta potential was good enough to produce formulations with good stability. The SEM analysis of batch F5 demonstrates that the nanosponges are segregated, spherical in shape with smooth surface and are porous in nature with particle size less than 1μ. Conclusion: Nanosponges loaded Hydrogel of Metformin HCl for the treatment of Psoriasis was successfully formulated, optimized and evaluated.
Keywords: Nanosponges; Metformin Hydrochloride; Topical Drug Delivery; Hydrogel; Psoriasis